Microcontroller Based Adjustable Speed Closed-Loop DC Motor Drive - S. Ettomi Ali, Yousef (2004)
The speed control of DC motors is very crucial especially in applications where precision and protection are of importance. This work investigates and implements a microcontroller-based adjustable speed drive system for a DC shunt motor. The theory of the armature voltage control algorithm in a closed loop system has been successfully implemented. An IGBT switch is used in buck configuration to control the armature voltage of the motor. The PWM signal that controls the IGBT is generated from a Motorola 68HC11 microcontroller. The speed of the motor is measured by a shaft encoder and directly fed to the microcontroller along with a speed reference signal.A data acquisition routine reads the measured speed and the reference speed in digital format and generates the error value signal. The error value signal is directly fed into the proportional controller routine to commute the controller output. Finally, the controller output is used to generate a PWM, which completes the loop by controlling the switch. To protect the motor from high current, a current monitoring routine is implemented to read the motor current through a Hall effect sensor. If the motor current is higher than its rated current halting the PWM generation routine will stop it. Experimental results obtained have supported the idea of the design. The speed of the motor could be controlled over a wide range using the dc chopper and the PWM. Employment of a microcontroller has shown a great improvement in the acceleration, speed reduction, and deceleration and over current protection of a dc motor.